Furanosyl Oxocarbenium Ion Conformational Energy Landscape Maps as a Tool to Study the Glycosylation Stereoselectivity of 2‐Azidofuranoses, 2‐Fluorofuranoses and Methyl Furanosyl Uronates. Issue 29 (17th April 2019) - van der Vorm, Stefan; Hansen, Thomas; van Rijssel, Erwin R.; Dekkers, Rolf; Madern, Jerre M.; Overkleeft, Herman S.; Filippov, Dmitri V.; van der Marel, Gijsbert A.; Codée, Jeroen D. C.
Abstract: The 3D shape of glycosyl oxocarbenium ions determines their stability and reactivity and the stereochemical course of SN 1 reactions taking place on these reactive intermediates is dictated by the conformation of these species. The nature and configuration of functional groups on the carbohydrate ring affect the stability of glycosyl oxocarbenium ions and control the overall shape of the cations. We herein map the stereoelectronic substituent effects of the C2‐azide, C2‐fluoride and C4‐carboxylic acid ester on the stability and reactivity of the complete suite of diastereoisomeric furanoses by using a combined computational and experimental approach. Surprisingly, all furanosyl donors studied react in a highly stereoselective manner to provide the 1, 2‐ cis products, except for the reactions in the xylose series. The 1, 2‐ cis selectivity for the ribo ‐, arabino ‐ and lyxo ‐configured furanosides can be traced back to the lowest‐energy 3 E or E 3 conformers of the intermediate oxocarbenium ions. The lack of selectivity for the xylosyl donors is related to the occurrence of oxocarbenium ions adopting other conformations. Abstract : Explaining selectivity : A combined experimental and computational approach is used to investigate the stereoselective outcome of glycosylation reactions of differentially substituted furanoses. A high 1, 2‐ cis selectivity was found for the ribo ‐, arabino ‐ and lyxo ‐configured furanosides, whereas the xylosyl derivatives show a lack of selectivity (see figure).